Solve the inequation: lo g [ 1 0 x 2 − 1 2 x + 3 0 ] [ lo g 2 5 2 x ] > 0
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Calm down! In general, lo g b a > 0 ⇔ { b > 1 and a > 1 0 < b < 1 and 0 < a < 1 . or
We must therefore determine the set ( A ∩ C ) ∪ ( B ∩ D ) , with the sets A , B , C , D defined as the solution sets: ( A ) : 1 0 x 2 − 1 2 x + 3 0 > 1 ( B ) : 0 < 1 0 x 2 − 1 2 x + 3 0 < 1 ( C ) : lo g 2 5 2 x > 1 ∴ 5 2 x > 2 ( D ) : 0 < lo g 2 5 2 x < 1 ∴ 1 < 5 2 x < 2
The solutions sets are A = ⟨ ← , 2 ⟩ ∪ ⟨ 1 0 , → ⟩ ; B = ⟨ 2 , 6 − 6 ⟩ ∪ ⟨ 6 + 6 , 1 0 ⟩ ; C = ⟨ 5 , → ⟩ ; D = ⟨ 2 5 , 5 ⟩ .
The solution set of the inequality is therefore ( A ∩ C ) ∪ ( B ∩ D ) = ⟨ 1 0 , → ⟩ ∪ ⟨ 2 5 , 6 − 6 ⟩ .